Addressing Youth Suicide Through School-Based Prevention and Postvention: Contemporary Scholarship Advancing Science, Practice, and Policy. Issue 3 (4th May 2022) - Espelage, Dorothy L.; Boyd, Rhonda C.; Renshaw, Tyler L.; Jimerson, Shane R.
Abstract: Youth suicide continues to be a significant public health issue, with especially elevated levels of suicide thoughts and behaviors experienced by marginalized students across race/ethnicity, gender, sexual orientation, and age demographics. This article highlights the importance of contemporary research informing and advancing professional efforts and also introduces a special topic section including eight articles that focus on key gaps in the literature related to mitigating suicide risk among youth in schools. Four survey studies and one systematic review aim to identify risk and protective factors for marginalized and understudied populations, with strong emphasis on cultural considerations around youth suicide; two studies center on the development and evaluation of school-based suicide prevention programs, with a focus on warning signs, professional development, and social validity; and the final paper focuses on learning from student perspectives to improve postvention. This special topic section represents the complexity of youth suicide prevention and postvention and offers school psychologists knowledge and strategies to prevent and intervene to reduce youth suicide. The introduction closes with several recommendations for further advancing science, practice, and policy related to mitigating suicide risk among youth in schools. IMPACT STATEMENT Prevention of youth suicide requires contemporary research and program development. School psychologists can play a critical role in preventing youth suicide through culturally relevant studies, evidence-based training and curriculum, and postvention strategies. Collectively, articles in this special series strengthen the literature for guiding school psychologists in mitigating suicide risk among youth in schools.